PERMAINAN PUZZLE AND BOTTLE CHALLENGE DALAM PEMBELAJARAN PAI MATERI SUJUD - Kholisoh Daimah; Nasrulloh Mubarok; Salsabila Salsabila; Lutfiatu Nafisah; Desi Ayu Kristiana (Tazkiya: Jurnal Pendidikan Islam, 2026)
This research is motivated by the importance of the prostration (sujud) material in Islamic Religious Education and Character Building (PAI) as a fundamental part of worship practices. However, in reality, many students experience difficulties in understanding the functions, implementation times, and memorizing the recitations of sujud. The purpose of this study is to help students better understand and master the material. The method used in this research is descriptive qualitative, with observation, interviews, and documentation as data collection techniques to obtain in-depth information. The results of the study indicate that the implementation of educational game media in the form of sujud puzzles and bottle challenges is able to improve conceptual understanding, practical skills, and students’ active involvement in learning activities. Thus, this strategy has proven effective in improving the quality of Islamic Religious Education learning, especially on the topic of the types of sujud